Les pratiques des gestes écocitoyens au Québec, une histoire d’âge et de famille - Dominique Morin; Bruno Bourliaguet; Hubert Armstrong; Marie-Andrée Leduc (Enfances, Familles, Générations, 2023)
Research framework : This article presents an analysis of Hydro-Québec residential customers’ responses which asked them to evaluate their household’s situation in terms of various environmental practices, eco-citizenship commitments and other aspects that distinguish their situation from that of other households.Objectives : To examine whether the occasional or regular practice of actions that can reduce electricity consumption is linked to others eco-citizenship practices. Also, to describe the differences in the integration of these actions into routines and habits, according to the situation of the participant and their household during the stages of adulthood and residential, family and economic trajectories.Methodology : A multivariate, factorial and classification tree analyses of data from an Internet survey with a probabilistic sample of over 2,200 participants.Results : In Quebec, electricity-saving practices are statistically linked to water-saving practices, and not to other practices aimed at reducing the harmful effects of consuming material goods. The environmental practices studied generally appear to be more integrated into the daily lives of retired households, and less practised among younger people who work, or living with children or teenagers.Conclusions : The conclusions underline the value of tracking electricity-saving practices when dressing an overall portrait of eco-citizenship actions. They also discuss our ongoing qualitative study as part of an extension of this research. Contribution : The article provides a global representation of variations in the practice of the most common environmental actions, paying particular attention to the stages of adulthood and the presence of spouses and children of different ages in the household.